Psychopathy and prejudice: The mediating role of empathy, social dominance orientation and right‐wing authoritarianism. (6th October 2021) - Stathi, Sofia; Humayun, Sajid; Stoddart Isaac, Reay; McCarron, Demi M.
Abstract: A current shift in intergroup relations research aims to delve deeper into whether, and how, individual differences predict social attitudes. Recent research goes beyond the measurement of typical personality traits and focuses also on the subclinical area of malicious traits. The present studies aimed at exploring the role of one such trait, psychopathy, as a predictor of negative social attitudes. The role of empathy was examined as a key underlying process explaining the relationship between primary and secondary psychopathy and social attitudes. Study 1 ( N = 171) and Study 2 ( N = 332) demonstrated that when entered as simultaneous predictors of negative attitudes toward immigrants (Study 1) and racism (Study 2), only primary psychopathy emerged as a significant predictor. Study 1 further demonstrated that lower levels of empathy mediated the psychopathy—attitudes path. Study 2 decomposed empathy into cognitive and affective, and tested the explanatory role of social dominance orientation (SDO) and right‐wing authoritarianism (RWA). Primary psychopathy predicted lower cognitive and affective empathy, which sequentially predicted racism via SDO (in the case of cognitive empathy) and RWA (in the case of affective empathy). The results are discussed in the context of an integration between the personality and intergroup relations literature.